2015
DOI: 10.1002/cne.23692
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal profiles of dental pulp nociception in rat cerebral cortex: An optical imaging study

Abstract: Somatosensation is topographically organized in the primary (S1) and secondary somatosensory cortex (S2), which contributes to identify the region receiving sensory inputs. However, it is still unknown how somatosensory inputs from the oral region, especially nociceptive inputs from the teeth, are processed in the somatosensory cortex. We performed in vivo optical imaging and identified the precise cortical regions responding to electrical stimulation of the maxillary and mandibular dental pulp in rats. Electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 43 publications
12
57
0
Order By: Relevance
“…Horinuki et al (17) reported that, in addition to S1, the cortical area caudally adjacent to the middle cerebral artery responds to electrical stimulation of maxillary and mandibular incisor and molar PDL. These anatomical findings indicate that the area corresponds to the secondary somatosensory cortex (S2) and oral region of the IC (IOR), as reported by Nakamura et al (49). S2/IOR receives varied somatosensory information from oral regions, including PDL sensation, gustation (50)(51)(52), and nociception (49,53,54).…”
Section: Cortical Responses To Pdl Stimulationsupporting
confidence: 75%
See 1 more Smart Citation
“…Horinuki et al (17) reported that, in addition to S1, the cortical area caudally adjacent to the middle cerebral artery responds to electrical stimulation of maxillary and mandibular incisor and molar PDL. These anatomical findings indicate that the area corresponds to the secondary somatosensory cortex (S2) and oral region of the IC (IOR), as reported by Nakamura et al (49). S2/IOR receives varied somatosensory information from oral regions, including PDL sensation, gustation (50)(51)(52), and nociception (49,53,54).…”
Section: Cortical Responses To Pdl Stimulationsupporting
confidence: 75%
“…These anatomical findings indicate that the area corresponds to the secondary somatosensory cortex (S2) and oral region of the IC (IOR), as reported by Nakamura et al (49). S2/IOR receives varied somatosensory information from oral regions, including PDL sensation, gustation (50)(51)(52), and nociception (49,53,54). Interestingly, electrical stimulation of S2/IOR induces rhythmic jaw movement (55,56).…”
Section: Cortical Responses To Pdl Stimulationsupporting
confidence: 73%
“…We consider that this application method allows the drugs to penetrate at least into the superficial layers (layers I-III), where application of voltage-sensitive dyes via the same method shows a sufficient penetration, as described in our previous study [8,25]. In addition, the same method for application of 6-Cyano-7-nitroquinoxaline-2,3-dione (CNQX) effectively suppresses excitatory propagation in the cortex [25], indicating a sufficient blockade of AMPA receptors.…”
Section: Electrical Stimulation and Drug Applicationmentioning
confidence: 98%
“…Next, we examined the effects of MOR, DOR, or KOR activation on excitatory propagation in S2/IOR in response to the maxillary molar pulp stimulation [7,8].…”
Section: Cortical Excitatory Propagation Responding To the Maxillary mentioning
confidence: 99%
See 1 more Smart Citation